Metastatic Chordoma: A Diagnostic Challenge on Fine Needle Aspiration - Ghassan Tranesh; Aziza Nassar (Case Reports in Pathology)
Chordomas are primary low grade malignant tumors of bone that usually arise within both ends of axial skeleton. The Notochord is a midline, ectoderm-derived structure that defines the phylum of chordates. Chordomas may pose difficult diagnostic challenges when encountered in secondary locations, such as lungs or other parenchymatous organs. We report the cytologic findings of a metastatic chordoma sampled through CT-scan guided fine needle aspiration (FNA) of lower lobe lung nodule in a 54-year-old man diagnosed with recurrent chordoma involving the lumber spine and paraspinal region.